Estimation of Corrosion-Free Life for Concrete Containing Ground Granulated Blast-Furnace Slag under a Chloride-Bearing Environment - Sung In Hong; Ki Yong Ann (Advances in Materials Science and Engineering)
The rate of chloride transport by diffusion in concrete containing ground granulated blast-furnace slag (GGBS) was mathematically estimated to predict the corrosion-free service life of concrete structures exposed to seawater environment. As a factor to corrosiveness of steel embedment, replacement ratio of GGBS was selected, accounting for 25 and 50% to total binder. As a result, it was found that an increase in the GGBS content resulted in an increase in the chloride binding capacity, which would give rise to a lower chloride diffusion rate, thereby reducing the risk of chloride-induced corrosion. When it comes to the sensitivity of parameters to service life, the effective diffusivity showed a marginal influence on serviceability, irrespective of GGBS contents while surface chloride content and critical threshold concentration revealed more crucial factors to long term chloride diffusion. As the GGBS replacement increased, the variation in service life has become less influential with changing parameters. Substantially, GGBS concrete at high replacement ratio enhanced the service life due to a combination of dense pore structure and enhanced chloride binding capacity.